Towards literacies of immanence: Getting closer to sensory multimodal perspectives on research. Issue 2 (June 2023) - Pool, Steve; Rowsell, Jennifer; Sun, Yun
In this article, we propose 'literacies of immanence' as a term for sensory-laden, embodied multimodal practices that happen when researchers get out of the way to allow for modal diversity in meaning making. The learning encounters that we observed during our research combined senses with a kaleidoscope of modes that were hard to describe through more traditional multimodal methods. Literacies of immanence is the most fitting phrase for these practices because they were fluid, open, and they did not rely on written and spoken texts. Researching in a primary and secondary special school that are part of an academy trust in the southwest of England, the research team engaged in research-creation propositions (Truman, 2021) where we watched and built on multimodal meaning making supplementing it with story-making activities. Writing and sharing fieldnotes and filming interactions, we abandoned original plans and instead shaped methods and theoretical framings around the population of learners we met. Fieldnotes were shared on a blog and filmmaking helped us to describe and draw out multimodal, immanent literacies and their epiphanic qualities. This article features fieldnotes along with images of multimodal-sensory encounters and ways that they helped us relate to the learners, their teachers and Head Teacher as well as each other as researchers. The article is of relevance to researchers looking for ways to capture visible and invisible modal practices at work across settings and a movement away from a definite or true-false rendering of multimodality to one that allows for divergent ways of being with modes.